Taurine: A Potential Ergogenic Aid for Preventing Muscle Damage and Protein Catabolism and Decreasing Oxidative Stress Produced by Endurance Exercise - De Carvalho, Flávia G.; Galan, Bryan S. M.; Santos, Priscila C.; Pritchett, Kelly; Pfrimer, Karina; Ferriolli, Eduardo; Papoti, Marcelo; Marchini, Júlio S.; de Freitas, Ellen C. (Frontiers in Physiology, 2017)
The aim of this study was to evaluate the effects of taurine and chocolate milk supplementation on oxidative stress and protein metabolism markers, and aerobic parameters in triathletes. METHODS: A double-blind, crossover study was conducted with 10 male triathletes, aged 30.9 ±1.3 yr, height 1.79 ± 0.01 m and body weight 77.45 ± 2.4 kg. Three grams of taurine and 400 ml of chocolate milk (TAUchoc), or a placebo (chocolate milk) (CHOC) was ingested post exercise for 8 weeks. Oxidative stress marker levels, and 24 hour urinary nitrogen, creatinine, and urea excretion were measured before and after 8 weeks of training and supplementation with TAUchoc or CHOC. A maximal incremental running test on a treadmill was performed in order to evaluate aerobic parameters: Vmax, heart rate (HR) and rate of perceived exertion (RPE). RESULTS: TAUchoc treatment during the 8 weeks resulted in increased taurine plasma levels (PRE 201.32± 29.03 µmol/L and POST 234.36±35.51 µmol/L, p= 0.01), decreased malondialdehyde levels (19.4%, p=0.03) and urinary nitrogen excretion (-33%, p= 0.03), and promoted positive nitrogen balance (p=0.01). There were no changes in reduced glutathione (TAUchoc PRE 0.72±0.08 mmol/L and POST 0.83±0.08 mmol/L; CHOC PRE 0.69±0.08 mmol/L and POST 0.81±0.06 mmol/L), vitamin E plasma levels (TAUchoc PRE 33.99±2.52 µmol/L and 35.95±2.80 µmol/L and CHOC PRE 31.48±2.12 µmol/L and POST 33.77±3.64 µmol/L), or aerobic parameters, which were obtained in the last phase of the maximal incremental running test (Vmax TAUchoc PRE 13±1.4 km/h and POST 13.22±1.34 km/h; CHOC PRE 13.11±2.34 km/h and POST 13.11±2.72 km/h), the heart rate values were TAUchoc PRE 181.89±24.18 bpm and POST 168.89±46.56 bpm; CHOC PRE 181.56±2.14 bpm and POST 179.78±3.4 bpm, and the RPE were TAUchoc PRE 8.33±2.4 AU and POST 9.1±2.1 AU; CHOC PRE 8.11±4.94 AU and POST 8.78±2.78 AU). CONCLUSION: Taurine supplementation did not improve aerobic parameters, but was effective in increasing taurine plasma levels and decreasing oxidative stress markers, which suggests that taurine may prevent oxidative stress in triathletes.